2016
DOI: 10.21111/at-tadib.v11i1.627
|View full text |Cite
|
Sign up to set email alerts
|

The Implementation of Collaborative Learning to Enhance the Students’ Critical Thinking In Writing

Abstract: The present study attempts to describe whether or not and to what extent Collaborative Learning can enhance the college students' critical thinking in writing, and identify the class climate when Collaborative Learning is implemented. The data of the research were obtained using several techniques including interview, observation, document, and test. The qualitative data were analyzed by using Constant Comparative Method, while the quantitative data were obtained by finding out the mean score of the two raters… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 3 publications
0
8
0
1
Order By: Relevance
“…Selain dapat meingkatkan kompetensi siswa pada aspek komunikasi, penerapan pembelajaran kolaboratif juga dapat meningkatkan kemampuan siswa dalam berpikir kritis dan memecah masalah secara kolaboratif (Anggraeni & Nilawijaya, 2021). Hasil penelitian Rokhaniyah (2016) menunjukkan bahwa penerapan model pembelajaran kolaboratif dapat meningkatkan kemampuan berpikir kritis, logis dan argumentatif siswa baik komunikasi oral maupun komunikasi tertulis. Hasil penelitian ini mengungkapkan siswa dapat membangun sebuah argumen yang sangat tajam dan logis melalui tulisan.…”
Section: Nounclassified
“…Selain dapat meingkatkan kompetensi siswa pada aspek komunikasi, penerapan pembelajaran kolaboratif juga dapat meningkatkan kemampuan siswa dalam berpikir kritis dan memecah masalah secara kolaboratif (Anggraeni & Nilawijaya, 2021). Hasil penelitian Rokhaniyah (2016) menunjukkan bahwa penerapan model pembelajaran kolaboratif dapat meningkatkan kemampuan berpikir kritis, logis dan argumentatif siswa baik komunikasi oral maupun komunikasi tertulis. Hasil penelitian ini mengungkapkan siswa dapat membangun sebuah argumen yang sangat tajam dan logis melalui tulisan.…”
Section: Nounclassified
“…Critical thinking as a valuable tool provides the avenue for students to make informed decisions about their knowledge, attitudes and abilities in academic endeavours (Kusumoto, 2018). Based on the foregoing assertion, Rokhaniyah (2016) reported that critical thinking affected students positively as they could express themselves confidently and became more creative. Sahoo and Mohammed (2018) analysed the reflections of a group of Korean medical students and indicated that the majority of the participants reported an improvement in their…”
Section: Critical Thinking and Collaborative Learningmentioning
confidence: 99%
“…A study conducted by Rokhaniyah [10] found that implementing Collaborative Learning enhances the students' critical thinking and ability to write analytical exposition. Furthermore, Collaborative Learning can improve the classroom climate by increasing students' attention to the teaching and learning process, helping them feel more alive, increasing their responsibility to work in groups to solve problems in writing, and raising their self-confidence to express their ideas.…”
Section: Literature Reviewmentioning
confidence: 99%